Electronic structures of organometallic complexes of f elements. Part 54. Electronic Raman and f-f transitions in the low temperature vibrational spectra of Cp3Ce(NCCH3)2 - Amberger, Hanns-Dieter; Reddmann, Hauke; Schultze, Holger; Jank, Stefan; Kanellakopulos, Basil; Apostolidis, Christos (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2003)
A comparison of the low temperature Raman spectra of Cp(3)Ce(NCCH(3))(2) (1), Cp(3)La(NCCH(3))(2) (2), Cp(3)La(NCCH(3))(2):Pr(3+) (3), Cp(3)La x NCCH(3) (4), Cp(3)Ce x NCCH(3) (5) and Cp(3)Tb x NCCH(3) (6) shows that the former compound exhibits three additional bands at 320, 2129 and 2154 cm(-1), which we ascribe to electronic Raman transitions. The two latter signals also appear in the low temperature IR spectrum of complex 1, but not in those of compounds 2-6. By performing crystal field (CF) calculations, the terminal states of the observed electronic Raman transitions could be identified. On the basis of both experimental and calculated CF energies as well as calculated wave functions the observed temperature dependence of mu(2)(eff) of complex 1 could be simulated in a satisfactory manner. A comparison of the low temperature Raman spectrum of compound 1 with the low temperature FIR spectrum of complex 2 shows that the selection rules for trigonal-bipyramidal coordination do not hold strictly for the skeletal vibrations. If the additional criterion of allowed vibronic side bands is applied to the transitions Gamma(1)-->Gamma(1, 4, 5, 6) of compound 3, the observed vibrational energies may be partly classified according to their symmetry.